The interconnection between second language teachers' language assessment literacy and professional agency: The mediating role of institutional policies. (December 2021) - Mansouri, Behzad; Molana, Khazar; Nazari, Mostafa
Abstract: Informed by Buchanan's (2015) conceptualization on the role of institutional idiosyncrasies in shaping teachers' agentive decisions as part of their identity construction, this study examines how 13 Iranian EFL teachers developed their language assessment literacy and how it discursively contributed to their professional identity and agency within their local context. Data were collected using an open-ended questionnaire, classroom observations, simulated recalls, and semi-structured interviews, and analyzed via thematic analysis principles. The findings showed that although the teachers implemented assessment practices that measured students' ability from multiple dimensions, the assessment policies of the school limited the teachers in selecting and enacting their preferred assessment practices. Additionally, while teachers represented the current standards of assessment in their accumulated assessment literacy, they felt as agentively ill-disposed assessors due to the institutional pressure sanctioning their autonomy in implementing the assessment practices. In this regard, the institutional context and the policies worked as a site where the teachers needed to adjust practicing their assessment literacy and hence adjusting their identity and agency. The study concludes with implications for language teachers and educational policy makers with regard to aligning language assessment literacy and teachers' professional agency and identity.